(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Post the economic reforms of 1991, there was an enhanced participation from private sector in the development of power projects in India. Development of power projects is a complex process in India with involvement of several stakeholders. Consequently there are several risks associated with the project at varied levels. Diverse stakeholders can bring about unforeseen conflicts which can hinder the successful completion of projects. As of year 2017, about 34 coal based power projects have been identified as stressed assets. Nearly 40% of the stressed capacity is still under development. This scenario points to the need of a proper risk assessment. The risk assessment for development of power projects often involves multiple variables and is fuzzy in nature and hence, it is appropriate to adopt the fuzzy synthetic evaluation method for risk assessment. This paper used the fuzzy synthetic evaluation model for assessing the risk level in development of power projects in India by analyzing several risk factors and risk groups based on the perceptions of experienced power sector professionalsi